Effectiveness of Japanese encephalitis vaccination among children in central India. Issue 1 (19th December 2022) - Tandale, Babasaheb V.; Khude, Poornima M.; Deshmukh, Pravin S.; Narang, Rahul; Qazi, Mohiuddin S.; Padmaja, Goteti V.; Jain, Manish; Jain, Dipty; Guduru, Vijay Kumar; Deshmukh, Pradeep R.; Raut, Abhishek V.; Narlawar, Uday W.; et al.
Abstract: Japanese encephalitis (JE) disease among children continues in central India despite vaccination implemented in the routine immunization program. Therefore, we planned to estimate the JE vaccination effectiveness among children by undertaking a 1:2 individually‐matched population‐based case‐control study from August 2018 to October 2020. The laboratory‐confirmed JE cases aged 1–15 years were enrolled along with neighborhood controls without fever and encephalitis matched on the residence area, age and sex. The JE vaccination history was enquired from parents and verified independently from the vaccination cards available at home and records at health facilities. We enrolled 35 JE cases and 70 matched controls. The vaccination effectiveness of 86.7% (95% confidence interval [CI]: 30.8–94.7) was estimated on the per‐protocol analysis of 31 case‐control sets. The screening method provided an effectiveness of 89.5% (CI: 78.9–94.7) on using the population vaccination coverage of 90% reported earlier in the same area. In conclusion, JE vaccination offered a moderate level of protection among children in JE medium‐endemic central India, similar to reports from high‐endemic areas in India. The operational aspects of vaccination program implementation need to be evaluated to assess the impact of vaccination on the disease burden of JE in medium‐endemic regions of India.